2004
DOI: 10.1259/dmfr/68039278
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic examination of mesiodens and their associated complications

Abstract: Although mesiodentes are not caused by malocclusion, they may cause it. A long period of impaction of mesiodentes may bring about dentigerous cyst formation or movement of the mesiodentes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
100
6
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 5 publications
16
100
6
6
Order By: Relevance
“…The shape of mesiodens may vary from a simple conical form to a larger, more complicated crown shape with a number of tubercles (3)(4)(5)(6)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Conical mesiodens is more common, and is more likely to erupt between the central incisors as a diminutive but fully developed tooth (3-7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The shape of mesiodens may vary from a simple conical form to a larger, more complicated crown shape with a number of tubercles (3)(4)(5)(6)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Conical mesiodens is more common, and is more likely to erupt between the central incisors as a diminutive but fully developed tooth (3-7).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this difference might be that the present series included children aged between 4 and 14 years. Asaumi et al (10) reported 51 cases of mesiodens in patients over 20 years of age; 19 (37%) had dentigerous cyst formation, and only 3 cysts were discovered in patients aged under 19 years. Primosch (16) reported an enlarged follicular sac in 30% of cases, but histological evidence of cyst formation was available in only 4-9%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They might cause clinical complications like retention of the primary teeth, delayed/failure of eruption of permanent teeth, ectopic eruption, rotation of adjacent teeth, root resorption, abnormal diastema, formation of dentigerous and primodial cysts, hence requiring surgical or orthodontic intervention. 1,[4][5][6][7][8] This study was conducted to determine radiographic features and management of mesiodens in the Department of Pediatric Dentistry at Kantipur Dental college and hospital.…”
Section: Introductionmentioning
confidence: 99%